Bean maize behavior applying fertilizers of marine origin as an alternative to synthetic fertilization - Moreno-Reséndez, Dr. Alejandro; Cantú- Brito, Jesús Enrique (Revista Mexicana de Ciencias Agrícolas, 2017)
The study was carried out to determine the effect of fertilizers of marine origin on the yield and quality of forage maize. The sowing was done in dry and four days after the first irrigation was applied: in total were four irrigations, distributed every 28-30 days, accumulating a lamina of 80 cm. The variables evaluated were: emergence, root development, vigor and plant height, and forage yield, green and dry. An experimental design randomized blocks with two treatments with 16 replications. The marine fertilizers caused significant differences ( p ≤ 0.05) between treatments regarding plant height, at least one sampling date, as well as green and dry fodder. In percentage terms plant height, fresh and dry forage plants receiving manure, recorded values of 12.8, 31.8 and 30.8% higher than the control plants treatment.
Keywords: Zea mays L.; organic fertilizers; fertilization; performance